Plotting Ilustrado: Fragments, Layers, and Blank Spaces in Miguel Syjuco’s Postmodern Narrative and Metadiscourse in the Search for the Great Filipino Novel - Natividad, Carolyn Pile (Archīum Ateneo, 2018)
Miguel Syjuco’s Ilustrado begins with the illusion of convention that lulls readers into complacency. As readers follow the story and find their feet, however, the path begins to crack. What begins as a novel about a search for The Great Filipino Novel turns into a postmodern narrative and metadiscourse on the vanity of such a search—punctuated and conditioned by fragments, layers, and blank spaces.